The study of relationship between working conditions and job satisfaction / Nurul Atika Samat - Samat, Nurul Atika (2011)
This research is about a study of relationship between working conditions and job satisfaction in Majlis Amanah Rakyat (MARA) Melaka. The factors the influence the job satisfaction are a management support, workstation ergonomic, workplace relationship and job security. The survey was conducted in MARA Melaka. The sample size of this study was 60 respondents who are the employees of the organization. Data was obtained using primary data. Respondents were required to answer the questionnaires that included the statement of each variable. Once the necessary data was collected, the data was analyzed and summarized in a readable and easily interpret form. The Statistical Package for Social Science (SPSS) version 18 was used to summarize data. The results are in form of reliability testing, T-test, Pearson Correlation analysis and multiple. Based on this research, the result indicated that all the factors are correlated where it refer that there significant between independent variable (management support, workstation ergonomic, workplace relationship and job security) and dependent variable ( job satisfaction). The conclusion of the study is the outcome of the survey analysis and findings. Finally, on the finding, some recommendations have been suggested in order to improve the level of satisfaction in MARA Melaka